Photosynthetic Efficiency is Higher in Asymmetric Leaves than in Symmetric Leaves of the Same Plant - Kozlov MV; Zverev V; Sandner TM (MDPI, 2022)
Symmetry pervades nature, but asymmetry is also rather common. Deviations from genetically programmed symmetry are usually associated with internal or external developmental disturbances and may therefore be related to imperfections in physiological processes. In this study, we test the hypotheses that the photosynthetic efficiency of individual leaves of a plant is negatively related to their asymmetry. We measured chlorophyll fluorescence in leaves of three woody species (Betula pubescens, Populus tremula and Salix caprea) in early and late summer in two localities situated ca. 1000 km apart, and we quantified the asymmetry of these leaves by a multivariate measure based on the relative positions of several landmarks. Contrary to our expectation, we found that the photochemical efficiency of photosystem II was positively correlated with leaf fluctuating asymmetry; this effect was weak but consistent across the studied plant species, localities and seasons. Our finding adds to limited evidence that within-plant variation in leaf asymmetry is associated with variation in leaf physiology. Irrespective of the underlying mechanisms, which remain unknown, the results suggest that trees may benefit even more from their asymmetric leaves, at least in terms of photosynthesis, than they do from their more symmetric leaves.